the impact of financial requirements and gender variables on the relationship between organizational commitment and work rotation intentions among health sector nurses in Setif- (the health’s sector of El-eulma as a model) - lakehal, Tahar; Baghoul , Zouhir (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
This paper discusses the impact of variable financial requirements and gender variable as a moderator of the relationship between their organizational commitment and turnover intention. Hypotheses were tested by Hierarchical Multiple Regression using a sample of nurses from the Public Establishment of Health of proximity of El Eulma city. The results indicated varying stronger relationships between components of organizational commitment and intentions to leave work. It has further strengthened the negative correlation more clearly by 9.2% in the relationship between continuous loyalty and Duran's intentions, making nurses with greater life commitments more connected to work despite the stressors of work, working hours and night shifts experienced by health sector nurses. It means that what reduces the intentions of leaving work is not that happiness at work or that sense of membership, belonging to the profession and organization (emotional loyalty 1 percent) and not out of their belief that they should stay in the sanatoriums in consideration of the health of patients (standard loyalty 3.2 percent) but that fear of not having or not getting another job and the lack of options as well as the costs of leaving the job.